The Sustainability of Digital Networks and Globalisation, the Key to Resilience? - Emilia Titan; Simona-Andreea Apostu; Mihaela Mihai; Dorel Paraschiv; Daniela Manea (Amfiteatru Economic, 2023)
Rethinking the concept of resilience in the post-pandemic period is urgently needed considering an uncertain and unpredictable future. To identify the necessary solutions for the recovery of the economy, the involvement of all actors in the socio-economic and political environment is vital. Consolidating regional development, intensifying global cooperation, and developing sustainable business models in the field of digital entrepreneurship are necessary pillars in revitalising the economy and creating a sustainable economy. In this context, using data for the countries of the European Union, it was shown, using statistical methods of multivariate analysis, that globalisation and digitalisation are necessary to achieve resilience. Thus, new opportunities are opening up for creating development strategies that can prepare socio-economic systems for future shocks and uncertainties.
Keywords: L14; L26; C01; O52; 330; resilience; globalisation; digitalisation; networks; sustainability; multivariate analysis